A study of matendera traditional dance of the karanga people of Matsveru, Chivi - Mangobe, Memory (Midlands State University, 2019)
The study focused on studying Matendera traditional dance of the Karanga people of Matsveru. The main focus was to study the role that the dance serves to the community, the musical instruments and attire of the dance, the context in which it is performed and how it is performed. The study was motivated by the realisation that there are many Zimbabwean traditional dances that have not been documented and are no longer practised resulting in them having the risk of becoming extinct. A Qualitative approach in the form of an ethnographic study was used to collect data. Research instruments used in this study included unstructured interviews and participant observations. The targeted population was Chivi Central District, sampling from Matsveru area. Major findings where that Matendera dance is a children’s dance performed mainly for dandaro (whiling up time). The dance has a unifying role within the community and plays a major role in educating children n with an effort to instil good moral values within them. However, it was concluded that to date, the dance is rarely performed and is slowly becoming extinct as evidenced by some of the major musical instruments such as mutumba drums that have long stopped to exist in the community. Also, the dance is under siege as a result of new entertaining platforms that have made children stop gathering for such performances hence the need to study and document the dance. The researcher recommends that, through the implementation of the new curriculum which encourages the teaching of all cultural dances, Matendera dance be considered to enable future generation to appreciate their indigenous traditional cultures.